2016
DOI: 10.1111/1462-2920.13184
|View full text |Cite
|
Sign up to set email alerts
|

The genome analysis of CandidatusBurkholderia crenata reveals that secondary metabolism may be a key function of the Ardisia crenata leaf nodule symbiosis

Abstract: A majority of Ardisia species harbour Burkholderia sp. bacteria within specialized leaf nodules. The bacteria are transmitted hereditarily and have not yet been cultured outside of their host. Because the plants cannot develop beyond the seedling stage without their symbionts, the symbiosis is considered obligatory. We sequenced for the first time the genome of Candidatus Burkholderia crenata (Ca. B. crenata), the leaf nodule symbiont of Ardisia crenata. The genome of Ca. B. crenata is the smallest Burkholderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 79 publications
(131 reference statements)
1
93
1
2
Order By: Relevance
“…Indeed, several studies [46, 47] previously demonstrated that the categories translation (J) and replication (L) showed a strong negative correlation with genome size, while transcription (K) showed a strong positive correlation with genome size. Similarly, Carlier et al [48, 49] showed that the genomes of the obligate leaf nodule endosymbionts Candidatus Burkholderia crenata and Candidatus Burkholderia kirkii were smaller, enriched in COG categories J and L and deprived in COG category K when compared to free-living, facultative endophytic Burkholderia species. Consequently, we may expect that larger genomes require greater regulatory capacity to control their versatile metabolic capacity, as reflected by the higher number of transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies [46, 47] previously demonstrated that the categories translation (J) and replication (L) showed a strong negative correlation with genome size, while transcription (K) showed a strong positive correlation with genome size. Similarly, Carlier et al [48, 49] showed that the genomes of the obligate leaf nodule endosymbionts Candidatus Burkholderia crenata and Candidatus Burkholderia kirkii were smaller, enriched in COG categories J and L and deprived in COG category K when compared to free-living, facultative endophytic Burkholderia species. Consequently, we may expect that larger genomes require greater regulatory capacity to control their versatile metabolic capacity, as reflected by the higher number of transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Recently,w es equenced the genome of the bacterial leaf symbiont. [1] Analysis of the genome sequence revealed essential pathways to be malfunctional, highlighting the advanced evolutionary stage of this plant-bacterium symbio-sis and ongoing genome reductive evolution. In that study,the putative FR biosynthetic gene cluster frs (Table S1), encoding anonribosomal peptide synthetase (NRPS), was identified on an extrachromosomal plasmid.…”
mentioning
confidence: 99%
“…Unexpectedly,b ioinformatic analysis of the frs genes revealed the presence of two thioesterase (TE) domains, representing two NRPS machineries,w hich together display ac lear colinearity between module and domain architecture and FR structure ( Figure 2). [1] To further analyze the FR-NRPS,wefirst investigated the Frscondensation (C) domains through bioinformatics.T his was done to classify Cdomains by function, such as epimerization and acceptance of acyl groups, l-, or d-amino acids. [8] We aligned the Cdomain sequences with available sequences based on the NaPDoS [9] database to construct ap hylogenetic tree ( Figure S2), which confirmed most of the features,such as transfer of acyl units, proposed for the FrsA and FrsD Cdomains.…”
mentioning
confidence: 99%
“…Reductive genome evolution, a process by which the size and coding capacity of genomes tends to shrink over time, is a nearly universal phenomenon among vertically transmitted symbionts and obligate pathogens, including leaf nodule symbionts of Rubiaceae and Primulaceae [1012, 36, 37]. The genome of O. dioscoreae LMG 29303 ⊤ is of average size for the family Alcaligenaceae (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Typical of vertically-transmitted symbiotic bacteria, Ca . Burkholderia leaf nodule symbionts show extensive signs of reductive genome evolution, with coding capacities ranging from 41.7 % to 67.3 % and an accumulation of pseudogenes and insertion sequences [1012]. Despite extensive genome erosion, some symbionts have been shown to produce secondary metabolites, likely involved in the protection of the host from herbivory, such as the insecticidal kirkamide and the depsipeptide FR900359, as well as the herbicidal streptol-glucoside possibly involved in allelopathic interactions [1214].…”
Section: Introductionmentioning
confidence: 99%